Implementation of Project-Based Evaluation (Project-Based Assessment) in Measuring Understanding of Islamic Values in Grade 1 Students of SDIT Al Uswah Pamekasan - Nurul Qomariyah; Heni Listiana (Perkumpulan Sarjana Pendidikan Islam Indonesia (PSPII) Wilayah Kalimantan Barat, 2025)
Abstract: This study aimed to describe the implementation of Project-Based Assessment in measuring first-grade students’ understanding of Islamic values at SDIT Al Uswah Pamekasan. It used a qualitative case study approach based on the need for assessment methods that covered cognitive, affective, and psychomotor aspects in early-grade Islamic Religious Education (PAI). Data were collected through observation, teacher interviews, and documentation of student projects. The findings showed that project-based assessment enabled creative and practical expression of Islamic values, increased student participation, and indirectly involved parents. It also revealed value internalization more authentically than written tests and served as a strategic alternative for more comprehensive PAI assessment at the primary level. Keywords: Project-based evaluation, Islamic values, Islamic Religious Education. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan implementasi Project-Based Assessment dalam mengukur pemahaman nilai-nilai Islam pada siswa kelas satu di SDIT Al Uswah Pamekasan. Penelitian ini menggunakan pendekatan studi kasus kualitatif berdasarkan kebutuhan metode penilaian yang mencakup aspek kognitif, afektif, dan psikomotorik dalam pembelajaran Pendidikan Agama Islam (PAI) pada kelas awal. Data dikumpulkan melalui observasi, wawancara guru, dan dokumentasi proyek siswa. Hasil penelitian menunjukkan bahwa penilaian berbasis proyek memungkinkan siswa mengekspresikan nilai-nilai Islam secara kreatif dan aplikatif, meningkatkan partisipasi siswa, serta melibatkan orang tua secara tidak langsung. Metode ini juga mengungkap internalisasi nilai secara lebih autentik dibandingkan tes tertulis dan menjadi alternatif strategis untuk penilaian PAI yang lebih komprehensif di tingkat pendidikan dasar.